2022
DOI: 10.1021/acssuschemeng.2c05172
|View full text |Cite
|
Sign up to set email alerts
|

Direct Ethyl Levulinate Production from Raw Lignocellulosic Biomass Mediated by a Novel Taurine-Based Imidazolium Ionic Liquid

Abstract: In this work, a novel renewable taurine-based ionic liquid (IL), [TauIm][HSO 4 ], was synthesized via the Debus− Radziszewski reaction. The synthesized IL was then used to produce ethyl levulinate (EL) from several lignocellulosic substrates under microwave irradiation. Experimental conditions (temperature, time, and IL quantity) for EL production from a model substrate (microcrystalline cellulose, MCC) were first investigated by design of experiment (DoE) using a central composite design (CCD). The highest E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…These advantages make ILs promising materials in carbohydrate science and technology. [70][71][72][73][74][75][76][77] ILs engage in complex interactions involving Coulomb forces, hydrogen bonds, and van der Waals forces. 78 These facilitate interactions with polysaccharides, resulting in successful solubilization.…”
Section: Ionic Liquids (Ils)mentioning
confidence: 99%
See 1 more Smart Citation
“…These advantages make ILs promising materials in carbohydrate science and technology. [70][71][72][73][74][75][76][77] ILs engage in complex interactions involving Coulomb forces, hydrogen bonds, and van der Waals forces. 78 These facilitate interactions with polysaccharides, resulting in successful solubilization.…”
Section: Ionic Liquids (Ils)mentioning
confidence: 99%
“…175 A recent investigation by Zhou and colleagues 176 demonstrated that incorporated carboxylic acid anions displayed a tunneling effect with acylation reagents in imidazole-derived ILs, which promoted rapid and efficient homogeneous acylation of cellulose via dynamic hydrogen bonding. In another study, Gomes et al 73 employed a taurine-based IL, [TauIm][HSO 4 ], as both solvent and catalyst under microwave-assisted conditions (190 °C, 60 min, 10 eq. of IL) and achieved 81% yield of ethyl levulinate via the conversion of MCC as the feedstock.…”
Section: Solvent Effects In Carbohydrate Chemical Transformationsmentioning
confidence: 99%
“…The conversion of biomass into chemicals has become a priority for reducing dependence on fossil fuels and mitigating greenhouse gas emissions. Biomass is a renewable source of carbohydrates that immobilizes CO 2 , producing approximately 170 billion tons per year. , Lignin, a natural aromatic heteropolymer, accounts for ∼40% of the energy content and 10–35% of the weight of lignocellulosic materials . Lignin is composed of sinapyl alcohol, coniferyl alcohol, and p -coumaric alcohol, which are connected by β-O-4, β-5, 5-5, and other linkages. , Despite the abundance of lignin, only ∼3% is currently utilized for commercial applications, and the rest is typically burned, resulting in air pollution .…”
Section: Introductionmentioning
confidence: 99%